ADAMTS5 Deficiency Protects Mice From Chronic Tobacco Smoking-induced Intervertebral Disc Degeneration. Issue 20 (15th October 2017) - Ngo, Kevin; Pohl, Pedro; Wang, Dong; Leme, Adriana S.; Lee, Joon; Di, Peter; Roughley, Peter; Robbins, Paul D.; Niedernhofer, Laura J.; Sowa, Gwendolyn; Kang, James D.; Shapiro, Steven S.; et al.
Abstract : Study Design: ADAMTS5-deficient and wild type (WT) mice were chronically exposed to tobacco smoke to investigate effects on intervertebral disc degeneration (IDD). Objective: The aim of this study was to demonstrate a role for ADAMTS5 in mediating tobacco smoking-induced IDD. Summary of Background Data: We previously demonstrated that chronic tobacco smoking causes IDD in mice because, in part, of proteolytic destruction of disc aggrecan. However, it was unknown which matrix proteinase(s) drive these detrimental effects. Methods: Three-month-old WT (C57BL/6) and ADAMTS5 −/− mice were chronically exposed to tobacco smoke (four cigarettes/day, 5 day/week for 6 months). ADAMTS-mediated cleavage of disc aggrecan was analyzed by Western blot. Disc total glycosaminoglycan (GAG) content was assessed by dimethyl methylene blue assay and safranin O/fast green histology. Vertebral osteoporosity was measured by microcomputed tomography. Human nucleus pulposus (hNP) cell cultures were also exposed directly to tobacco smoke extract (TSE), a condensate containing the water-soluble compounds inhaled by smokers, to measure ADAMTS5 expression and ADAMTS-mediated cleavage of aggrecan. Activation of nuclear factor (NF)-κB, a family of transcription factors essential for modulating the cellular response to stress, was measured by immunofluorescence assay. Results: Genetic depletion of ADAMTS5 prevented vertebral bone loss, substantially reduced loss of disc GAG content, and completely obviated ADAMTS-mediated proteolysis of disc aggrecan within its interglobular domain (IGD) in mice following exposure to tobacco smoke. hNP cell cultures exposed to TSE also resulted in upregulation of ADAMTS5 protein expression and a concomitant increase in ADAMTS-mediated cleavage within aggrecan IGD. Activation of NF-κB, known to be required for ADAMTS5 gene expression, was observed in both TSE-treated hNP cell cultures and disc tissue of tobacco smoke-exposed mice. Conclusion: The findings demonstrate that ADAMTS5 is the primary aggrecanase mediating smoking-induced disc aggrecanolysis and IDD. Mouse models of chronic tobacco smoking are important and useful for probing the mechanisms of disc aggrecan catabolism and IDD. Level of Evidence: N/A